Study on shashi tharoor’s fiction and politics - DURGESH KUMAR (International Journal of Multidisciplinary Research and Studies, 2021)
Shashi Tharoor is an Indian former international civil servant, diplomat, bureaucrat, and politician, as well as a writer and public intellectual. He was born on March 9, 1956 in London, England, and he has been serving as the Member of Parliament for the constituency of Thiruvananthapuram in the state of Kerala since 2009. He is the current head of the Standing Committee on Chemicals and Fertilizers, where he has served for many years. Formerly holding the position of Under-Secretary General of the United Nations, he attempted to run for the position of Secretary-General in 2006 but was ultimately unsuccessful. He was once the Chairman of both the Parliamentary Standing Committee on External Affairs and the Parliamentary Standing Committee on Informational Technology before becoming the Founder-Chairman of the All India Professionals Congress. Tharoor was born in London, United Kingdom, but he spent his childhood in India. He received his undergraduate degree from St. Stephen’s College in Delhi in 1975 and his doctorate in International Relations and Affairs from the Fletcher School of Law and Diplomacy at Tufts University in 1978. Tharoor worked all over the world after completing his education. He received this honor from the Fletcher School when he was just 22 years old, making him the youngest person to ever do so at the time. Tharoor worked as an official with the United Nations from 1978 to 2007, during which time he rose through the ranks to become the Under-Secretary General for Communications and Public Information in 2001. After coming in second place in the election for U.N. Secretary-General in 2006 to Ban Ki-moon, he made the decision to resign and announced his decision.